2021
DOI: 10.1073/pnas.2021798118
|View full text |Cite
|
Sign up to set email alerts
|

HIPK2 phosphorylates HDAC3 for NF-κB acetylation to ameliorate colitis-associated colorectal carcinoma and sepsis

Abstract: Although inflammation is critical for the clearance of pathogens, uncontrolled inflammation also contributes to the development of multiple diseases such as cancer and sepsis. Since NF-κB–mediated transactivation in the nucleus is pivotal downstream of various stimuli to induce inflammation, searching the nuclear-localized targets specifically regulating NF-κB activation will provide important therapeutic application. Here, we have identified that homeodomain-interacting protein kinase 2 (HIPK2), a nuclear ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Furthermore, we found that Cox1, as the target gene downstream of NF-kB signalling, depends on HDAC3 regulation. As proven by a previous report, HDAC3 contains deacetylase (DA)dependent deacetylation of p65, in line with previous literature indicating that p65 is a direct substrate of HDAC3 and that deacetylation triggers the nuclear export of p65 (43,44). Therefore, HDAC3 regulating PGE 2 synthesis may be attributed to deacetylating p65, as our data proved.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we found that Cox1, as the target gene downstream of NF-kB signalling, depends on HDAC3 regulation. As proven by a previous report, HDAC3 contains deacetylase (DA)dependent deacetylation of p65, in line with previous literature indicating that p65 is a direct substrate of HDAC3 and that deacetylation triggers the nuclear export of p65 (43,44). Therefore, HDAC3 regulating PGE 2 synthesis may be attributed to deacetylating p65, as our data proved.…”
Section: Discussionsupporting
confidence: 92%
“…This explains older results showing that the C-terminus is necessary for catalytic activity (Yang et al, 2002). Since the C-terminus can be phosphorylated by several kinases (Sengupta and Seto, 2004; Seo et al, 2019; Tsai and Seto, 2002; Zhang et al, 2021; Zhang et al, 2005), it suggests that the HDAC3-DAD domain interaction is regulated by signaling. Furthermore, a recent study showed that NADPH inhibits HDAC3-DAD domain complex formation by competing with IP4 for binding to HDAC3 (Li et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…For HDAC3 phosphorylation, it is interesting that phosphorylated Ser424 increases HDAC3 activity, but several protein kinases are reported to be involved in, including CK2, TANK-binding kinase (TBK1), leucine-rich repeat kinase 2 (LRRK2), c-Jun N-terminal kinase (JNK), and PTEN-induced putative kinase 1 (PINK1) [ 139 143 ]. The other site, Ser374, is phosphorylated by homeodomain-interacting protein kinase 2 (HIPK2), which inhibits the enzymatic activity of HDAC3 [ 144 ]. Similarly, the enzymatic activity of HDAC8 is repressed by PKA-mediated phosphorylation at Ser39 [ 145 , 146 ].…”
Section: The Regulation Of Histone Deacetylases By Phosphorylationmentioning
confidence: 99%